Wearable biosensors have the potential to monitor physiological changes associated with opioid overdose among people who use drugs: A proof-of-concept study in a real-world setting. (1st December 2021) - Roth, Alexis M.; Tran, Nguyen K.; Cocchiaro, Ben; Mitchell, Allison K.; Schwartz, David G.; Hensel, Devon J.; Ataiants, Janna; Brenner, Jacob; Yahav, Inbal; Lankenau, Stephen E.
Abstract: Introduction: Wearable biosensors have the potential to monitor physiological change associated with opioid overdose among people who use drugs. Methods: We enrolled 16 individuals who reported ≥ 4 daily opioid use events within the previous 30 day. Each was assigned a wearable biosensor that measured respiratory rate (RR) and actigraphy every 15 s for 5 days and also completed a daily interview assessing drug use. We describe the volume of RR data collected, how it varied by participant characteristics and drug use over time using repeated measures one-way ANOVA, episodes of acute respiratory depression (≤5 breaths/minute), and self-reported overdose experiences. Results: We captured 1626.4 h of RR data, an average of 21.7 daily hours/participant over follow-up. Individuals with longer injection careers and those engaging in polydrug use captured significantly fewer total hours of respiratory data over follow-up compared to those with shorter injections careers (94.7 vs. 119.9 h, p = 0.04) and injecting fentanyl exclusively (98.7 vs. 119.5 h, p = 0.008), respectively. There were 385 drug use events reported over follow-up. There were no episodes of acute respiratory depression which corresponded with participant reports of overdose experiences. Discussion: Our preliminary findings suggest that using a wearable biosensor to monitor physiological changes associated with opioid use was feasible. However, more sensitive biosensors that facilitate triangulation of multiple physiological data points and larger studies of longer duration are needed. Highlights: A wearable biosensor was used to monitor respiratory rate among PWUD. Respiratory rate was captured for 1626.4 of 1800 possible follow-up hours. No instances of acute respiratory depression were detected. With refinement, biosensors could be used to intervene during solitary use events.